Persepsi Remaja tentang Pendewasaan Usia Perkawinan di Wilayah Kerja Puskesmas Air Putih Kota Samarinda - Ratna Wati; Khumairotul Zahro Al Ahmadi; Dyah Rahmawati; Annisa Nurrachmawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Marriage is a planned path and prepared to form a prosperous and happy family. However, child marriage is recognized as a detrimental practice. Field facts often ignore the priority of age maturity, maturity, mentality towards marriage. Early marriage is almost in all regions with a trend of first child marriage of girls before 18 years or 15 years. The background factors for early marriage are related to economics, education, parental coercion, customs and also because of pregnancy outside of marriage. Based on that, the researcher wants to raise the focus of the research, namely to explore in depth the perception of adolescents about the maturity of the age of marriage in the Air Putih Health Center work area. The purpose of the study is to explore in depth the perception of adolescents including knowledge related to the Maturation of the Age of Marriage, practice, views, and beliefs of social norms related to early marriage, adolescent behavior towards external motivation to marry early, and adolescent self-efficacy in maintaining attitudes to prevent early marriage in the Air Putih Health Center Work Area, Samarinda City. This type of research uses a qualitative method with a phenomenological approach. The informants of this study were male and female teenagers aged 16-18 years who lived in Samarinda City, whether or not they had received PUP information. The selection of purposive adolescent informants used intensity sampling techniques, accidental through searches with 5 research subjects consisting of 2 male teenagers and 3 female teenagers. The data collection technique used was in-depth interviews. Then the data obtained was analyzed and reduced through a coding system assisted by open code software, followed by categorization of open code output data. The output, adolescents with good economic status, educated parents, strong culture and traditions, is sufficient to realize PUP. Adolescent perceptions need to be strengthened by efforts to raise awareness of the importance of PUP through health education and efforts by community leaders. Keywords: Motivation, Leadership Style, Nurse’s Behavior, Medical Waste ABSTRAK Pernikahan ialah jalan terencana juga disiapkan guna terbentuknya sebuah keluarga sejahtera juga bahagia. Namun, pernikahan anak diakui selaku praktik merugikan. Fakta lapangan banyak pengabaian keutamaan pematangan usia, kedewasaan, mental menuju pernikahan. Pernikahan usia dini hampir diseluruh wilayah dengan tren perkawinan anak perempuan pertama sebelum 18 tahun ataupun 15 tahun. Adapun faktor latar belakang adanya pernikahan dini terkait ekonomi, pendidikan, paksaan orang tua, adat istiadat juga sebab hamil di luar nikah. Berdasar itu, peneliti ingin mengangkat fokus penelitian yakni menggali secara mendalam persepsi remaja tentang pendewasaan usia perkawinan di wilayah kerja Puskesmas Air Putih. Tujuan penelitian guna penggalian mendalam persepsi remaja diantaranya pengetahuan terkait Pendewasan Usia Perkawinan, pengamalan, pandangan, juga keyakinan norma sosial terkait pernikahan dini, perilaku remaja ke motivasi ekternal untuk menikah dini, serta efikasi diri remaja atas pertahanan sikap pencegahan pernikahan dini di Wilayah Kerja Puskesmas Air Putih Kota Samarinda. Jenis penelitian ini bermetode kualitatif berpendekatan fenomenologi. Informan penelitian ini yakni remaja pria juga wanita 16-18 tahun yang tinggal di Kota Samarinda, baik pernah/belum mendapat informasi PUP. Pemilihan informan remaja purposiveberteknik intensity sampling, accidental lewat pencarian dengan subjek penelitian ini berjumlah 5 orang terdiri dari 2 remaja laki-laki juga 3 remaja Perempuan. Teknik pengumpulan data yang digunakan adalah wawancara mendalam (indepth interviews). Lalu perolehan data dianalisa dan direduksi lewat sistem coding berbantuan software open code, dilanjutkan pengkategorisasian data output open code. Outputnya, remaja berperekonomian baik, orang tua berpendidikan, budaya juga tradisi kuat, cukup guna mewujudkan PUP. Persepsi remaja perlu diperkuat dengan upaya penyadaran pentingnya PUP melalui pendidikan kesehatan juga upaya tokoh masyarakat. Kata Kunci: Pernikahan, Pernikahan Dini, Pendewasaan Pernikahan, Remaja, Persepsi